Effects of defoliation on vegetation growth in a semi-arid area of Kenya. 1. Annual dry matter production - Potter, H.L.; Said, A.N. (1986)
Reports the effects of various defoliation treatments on sward characteristics in Kenya with particular reference to productivity and persistence.